Assessing the microbiological quality of raw goats' and ewes' tank milk samples in Switzerland. (March 2020) - Friker, Brian; Morach, Marina; Püntener, Sabrina; Cernela, Nicole; Horlbog, Jule; Stephan, Roger
Abstract: In recent years, popularity of raw milk has increased in many industrialised countries. This study (i) enumerated total viable counts (TVC) and Escherichia coli counts, (ii) assessed prevalence of Staphylococcus ( S. ) aureus, Salmonella spp. and STEC, (iii) screened for methicillin resistant S. aureus (MRSA) and extended-spectrum β-lactamases (ESBL)-producing Enterobacteriaceae in sheep and goat tank milk samples collected throughout Switzerland and (iv) provided further strain characteristics on isolated pathogens and MRSA. One hundred and twenty-three tank milk samples from 116 farms were analysed. The median TVC was 3.8 log cfu mL −1 . E. coli was detected in 16 (13.0%) and S. aureus in 18 (14.6%) samples. Polymerase chain reaction for stx genes was positive in 14 (11.4%) samples. MRSA were isolated from 4 (3.3%) samples. Salmonella spp. and ESBL-producing Enterobacteriaceae were not isolated.